Формирование основ педагогического мастерства в современной школе - Балгабаева, Г.З.; Балгабаева, Г.З. (My University, 2016)
The basis of development of pedagogical mastery is an alloy of knowledge and professional orientation, a success condition is pedagogical abilities, the means giving integrity of professional activity of the teacher - abilities in the field of pedagogical equipment. Formation of pedagogical mastery requires mastering the sum of knowledge, skills, abilities, development of professionally important qualities of the personality that is reached in the course of vigorous activity, independent work, accumulation of teaching experience, holding special events.
Keywords: pedagogical mastery; pedagogical abilities; formations; professionally; experience